Golden girls - Morgan, Melissa J. (New York, N.Y. : Grosset & Dunlap, 2007)
When Lainie invites her to spend time with the popular sixth division girls, Natalie forgets her Color War obligations and her promise to help best friend Tory to captain the fifth division blue team, but when she is noticed by a boy Lainie has a crush on, Nat has some apologies to make.
Keywords: Camps -- Fiction; Loyalty -- Fiction; Self-confidence -- Fiction; Popularity -- Fiction; Friendship -- Fiction